2006
DOI: 10.1007/s10682-006-9102-3
|View full text |Cite
|
Sign up to set email alerts
|

A trade-off between female lifespan and larval diet breadth at the interspecific level in Lepidoptera

Abstract: A prediction arising from several evolutionary diet breadth models is that, in insect herbivores whose adults practise adaptive host plant selection based on larval performance, female adult lifespan should be negatively correlated with larval diet breadth. In one category of models, female adult lifespan drives evolutionary changes in larval diet breadth; in the other category, larval diet breadth drives evolutionary changes in female adult lifespan. Applying the method of independent contrasts to a biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 76 publications
(90 reference statements)
0
34
1
Order By: Relevance
“…Subsequently, because high quality eggs impose an increase in the metabolic rates, females may additionally experience reduced longevity [13], [14], [15], [65], [66], [67]. Because previous studies explored only the effects of low temperatures on one generation, positive physiological adaptation transmitted to the next generation remained hidden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, because high quality eggs impose an increase in the metabolic rates, females may additionally experience reduced longevity [13], [14], [15], [65], [66], [67]. Because previous studies explored only the effects of low temperatures on one generation, positive physiological adaptation transmitted to the next generation remained hidden.…”
Section: Discussionmentioning
confidence: 99%
“…development and fecundity) of the offspring [2], [3], [4], [9]. Many previous studies have shown that insect’s growth and population development in progeny were influenced by their mother’s experiences of temperature changes [10], [11], [12], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22]. For example, repeated exposition to cold temperatures in female flies resulted in a change in sex ratio and number of offspring [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…2005). At higher temperatures, they may also be allocating signiÞcantly more energy resources to egg production than maintenance of body functions, thereby resulting in reduced performance and survival (Papaj 2000;Carey 2001;Jervis et al 2005Jervis et al , 2007. It is plausible that at 22.5 and 35ЊC, L. reticulatus has a proportionately shorter egg-laying period than at optimal temperatures because of the diversion of resources from egg production and maturation that may occur at these suboptimal temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results agree with the work of Bonato (1999) and Ullah et al (2011), who observed that the oviposition period and adult longevity of T. evansi, Table 2 T. merganser and T. kanzawai decreased in response to temperature increase. They found that lower temperatures extended the duration of the egg-laying period, which could be explained by reduced activity, less energy used for reproduction, or both (Papaj 2000;Carey 2001;Jervis et al 2005Jervis et al , 2007Berger et al 2008). Fecundity was highest at 25-30°C.…”
Section: Discussionmentioning
confidence: 99%